The positive effects of dietary inositol on juvenile hybrid grouper (♀Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu) fed high-lipid diets: Growth performance, intestinal digestive enzymes, tissue morphology, and intestinal microbiota - Biao Li; Simiao Pan; Weibin Huang; Menglong Zhou; Hao Liu; Baiquan Lu; Hengyang Song; Wenshan Cai; Beiping Tan; Yuanzhi Yang; Xiaohui Dong (Aquaculture Reports)
The aim of study was to explore the beneficial effects of adding inositol to high-lipid diets on intestinal digestive enzymes, tissue morphology, and intestinal microbiota in juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatu). Six isonitrogenous (CP 51 %) and isolipidic (CL 16 %) diets were formulated, each containing different levels of inositol: 0 % (J1, as the control group), 0.04 % (J2), 0.08 % (J3), 0.16 % (J4), 0.32 % (J5) and 0.64 % (J6) inositol. Grouper (initial body weight of 6.76 ± 0.34 g) were fed experimental diets continuously for 8 weeks. Results showed that inositol significantly increased the specific growth rate of J3, J4, J5, J6 groups compared to the control group (P > 0.05). Amylase, lipase, and trypsin activities generally increased with higher inositol levels. Amylase activities were significantly higher in J4, J5, and J6 groups compared to the control group (P < 0.05), while lipase and trypsin activities were significantly higher in all inositol-treated groups (P < 0.05). Inositol did not significantly affect intestinal plica height (P > 0.05), but increased plica width, muscularis thickness, and goblet cell number (P < 0.05). Analysis of intestinal microbiota revealed a higher number of OTUs in the J3 group compared to J1 and J6 groups (P < 0.05), with no significant differences in Ace and Chao1 indices (P > 0.05). The Simpson index was significantly higher in the J3 group compared to J1 group (P < 0.05), with no significant differences between J6 and J1, J3 groups (P > 0.05). The dominant intestinal phylum mainly consists of Proteobacteria and Cyanobacteria, while the dominant family mainly consists of Vibrionaceae and Burkholderiaceae. In summary, supplementing high-lipid diets with appropriate inositol can enhance digestive ability, improve the morphology of hybrid grouper intestines, increase the abundance of beneficial bacterial microbiota, maintain intestinal health, and promote growth.